Ocean Wave Measurement by TerraSAR-X - Waves Travelling into Sea Ice East Greenland Case - Lehner, Susanne; Gemmrich, Johannes; Pleskachevsky, Andrey; Gebhardt, Claus P.; Bidlot, J.; Rosenthal, Wolfgang (2015)
The new high resolution satellite TerraSAR-X allows the measurement of spectral ocean wave peak wavelength even below 30 meters wave length and is thus comparable to ocean wave measurements by ship radar. The theory of imaging of the moving sea surfaces by SAR has been discussed by many authors resulting in nonlinear schemes in need of a first guess from a wave model. For ENVISAT ASAR with a rather coarse resolution yielding the possibility to measure waves longer than 100 meters a first empirical algorithm to derive significant wave height from SAR data was derived.here we use a simple empirical approach called XWAVE derived from more than 500 TS-X scenes to measure sea state parameters from images of the X-band satellite TS-X. The sea state parameters derived are peak wavelength and travel direction as well as significant wave height of the 2D spectra. We discuss the observed relationship of energy maxima in wavenumber and frequency spectra of wave buoys in the image.Several case studies of TS-X images in respect to fetch laws, refraction and shoaling are given, showing the possibility to derive underwater bathymetry from the wave patterns.The data from TerraSAR-X and TanDEM-X satellites have as well been applied for investigating of sea surface motion in Polar Regions. The surface wave’s propagation in open water and with different ice coverage is studied with focus on different SAR imaging mechanism of long waves. A combination of wave height and wavelength results in derivation of energy flux and its change allows qualitative evidence of the damping mechanism of waves in sea ice and thus of sea ice parameters. The different ice coverage provokes differences of the SAR imaging of waves propagating into ice covered regions. Typical “Dragon armor scale” structures are observed in areas where ocean waves travel in areas covered with ice floes. The parameters of sea state and spectral parameters of such texture are both analyzed and show the differences in sea state propagation and imaging of water with and ...